New data on the European species of three genera Scelionidae (Hymenoptera) - Pintureau, Bernard; Al-Nabhan, Mounir (Zootaxa, 2003)
Among the Scelionidae recently collected in several countries, mainly from Europe, the genus Gryon was represented by two species, the genus Baeus by one species and the genus Idris by three species. Four species are reported as new for France (two species of Gryon, one of Baeus and one of Idris), three as new for for Portugal (Azores) (one species of each of the three studied genera) and one as new for Syria (one species of Gryon). Improved morphological descriptions with illustrations are provided for several of the species. A new host (eggs of the pentatomid bug Eurygaster integriceps) is recorded for Gryon fasciatus Priesner.